Review of publications on the functioning of the tatar language in mass media in the Republic of Tatarstan - Kuzmina, Khalisa Kh. (2018)
Article represents results of review and partial content-analysis of two leading media in Tatar and Russian languages concerning exposure of language situation in the Republic of Tatarstan in 2017-2018. News net title ProKazan.ru (http://www.prokazan.ru), where news of city of Kazan are presented in Russian language, and leading information agency of the Republic of Tatarstan “Tatar-Inform” (http://www.tatar-inform.ru) in Tatar and Russian languages were analyzed. Major methods used in course of conduction of this study were description method and method of quantitative content-analysis in aggregate with their practices. Study showed that portal of information agency “Tatar-Inform” is more informative in quantitative and qualitative aspects of published materials; dominating genre in both portals is information message in form of notes and extended notes containing sufficiently large quantity of event details, give fact with details, opinions of competent persons; presence of mini-conclusion is possible; main theme at exposure of events related to functioning of Tatar and Russian languages in the Republic of Tatarstan is the theme of Tatar language teaching in educational system of the republic. Practical significance of the study is comprised in the fact than major provisions, recommendations and conclusion stated in this work may be used in in studies related to further development of the review and content-analysis of media; at teaching of courses on journalism and sociology; at composing of electronic media rating.